2003
DOI: 10.1093/molehr/gag036
|View full text |Cite
|
Sign up to set email alerts
|

A novel serine protease of the mammalian HtrA family is up-regulated in mouse uterus coinciding with placentation

Abstract: This paper characterizes a novel gene, previously identified as uniquely regulated at implantation in mouse uterus. We cloned its full mRNA sequence encoding a serine protease possessing an IGF-binding domain and named it pregnancy-related serine protease (PRSP). PRSP is structurally similar to mammalian HtrA1 (56% amino acid similarity). Northern analysis revealed that the expression of PRSP mRNA was low before pregnancy, but it was increased at implantation and markedly up-regulated post-implantation. In-sit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
83
1

Year Published

2005
2005
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 73 publications
(89 citation statements)
references
References 27 publications
5
83
1
Order By: Relevance
“…However, the highest level of HtrA1 expression was found in the human placenta, suggesting that HtrA1 may play important roles in placental formation and function (Nie et al, 2003a). Our recent studies demonstrated that HtrA1 was, indeed, tightly regulated during placentation in the mouse (Nie et al, 2005), and that its closely related family member, HtrA3, is also strongly associated with placental development both in the mouse and human (Nie et al, 2003b(Nie et al, , 2006a.…”
Section: Introductionmentioning
confidence: 94%
See 1 more Smart Citation
“…However, the highest level of HtrA1 expression was found in the human placenta, suggesting that HtrA1 may play important roles in placental formation and function (Nie et al, 2003a). Our recent studies demonstrated that HtrA1 was, indeed, tightly regulated during placentation in the mouse (Nie et al, 2005), and that its closely related family member, HtrA3, is also strongly associated with placental development both in the mouse and human (Nie et al, 2003b(Nie et al, , 2006a.…”
Section: Introductionmentioning
confidence: 94%
“…HtrA (high temperature requirement factor A) is a serine protease initially identified in Escherichia coli as a heat shock protein essential for bacterial survival at elevated temperature (Clausen et al, 2002). Four mammalian HtrA (1-4) proteins have now been identified, representing a novel family of serine proteases with each member containing a highly conserved trypsin-like catalytic domain followed by one or more C-terminal PDZ domains (Hu et al, 1998;Gray et al, 2000;Clausen et al, 2002;Nie et al, 2003b). HtrA1 was originally identified as a gene down-regulated in SV40-transformed fibroblasts (Zumbrunn and Trueb, 1996).…”
Section: Introductionmentioning
confidence: 99%
“…Total RNA was isolated and Northern analysis (15 g/lane) performed as previously published (Nie et al, 2000(Nie et al, , 2003b. A cDNA fragment of 488 bp of mouse HtrA1 mRNA (nt 411-898, accession no.…”
Section: Northern Blot Analysismentioning
confidence: 99%
“…HtrA1 expression was identified recently during mouse development (De Luca et al, 2004) and in several human tissues (De Luca et al, 2003), and high expression of HtrA1 was reported in the human placenta (Nie et al, 2003a). Of interest, significant up-regulation of HtrA3 expression was also identified during placentation in the mouse (Nie et al, 2003b), suggesting that HtrA proteases might play important roles in placental development and function.…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation